Antibiotic resistance patterns amongst clinical Vibrio cholerae O1 isolates from Accra, Ghana - Kuma, George Khumalo; Opintan, Japheth A; Sackey, Samuel; Nyarko, Kofi M; Opare, David; Aryee, Esther; Dongdem, Anthony Z; Antwi, Lorreta; Ofosu-Appiah, Lawrence H; Owusu-Okyere, Godfred; Asmah, Richard H (International Journal of Infection Control, 2014)
One of the protocols in the treatment and control of cholera infection is antibiotic therapy. However, increasing rates of antibiotic resistance amongst enteric bacteria including Vibrio cholerae have been reported in recent times. There has been no continuous surveillance on antibiotic susceptibility profiles for V. cholerae O1 in Ghana. This study determined resistance profiles of V. cholerae O1 to selected and commonly used antimicrobial agents and assessed resistance patterns across year periods. Additionally, the range of antibiotics currently effective for treatment and infection control during cholera outbreaks was ascertained. We screened a cumulative total of 277 isolates archived between 2010 and 2012 from the Greater Accra Region-Ghana, using the disc diffusion method. The recommendations of the Clinical Laboratory and Standards Institute were used to interpret our results. Resistance patterns were high for co-trimoxazole 232/241(96.3%), trimethoprim 265/276 (96.0%), erythromycin 255/270 (94.4%), and were low for azithromycin 0/11(0%), ciprofloxacin 1/274(0.4%), doxycycline 40/235(14.5%) and tetracycline 43/232(15.6%). There was significant association between antibiotic susceptibility patterns over the period of years for all antibiotics tested except ciprofloxacin (P=0.5089), trimethoprim (P=0.0533) and erythromycin (P=0.3200). High levels of antibiotic resistance among the present population of V. cholerae O1 isolates were observed. However, during cholera outbreaks, azithromycin, ciprofloxacin, doxycycline and tetracycline are alternatives in the treatment and control of infection when not contra-indicated.Key Words: Cholera outbreak, Infection control, Surveillance, Antibiotic Resistance, Vibrio cholerae.